Retrospective observational studies in ultra-rare sarcomas: A consensus paper from the Connective Tissue Oncology Society (CTOS) community of experts on the minimum requirements for the evaluation of activity of systemic treatments. (November 2022) - Stacchiotti, Silvia; Maria Frezza, Anna; Demetri, George D.; Blay, Jean-Yves; Bajpai, Jyoti; Baldi, Giacomo G.; Baldini, Elizabeth H.; Benjamin, Robert S.; Bonvalot, Sylvie; Bovée, Judith V.M.G.; Callegaro, Dario; Casali, Paolo G.; et al.
Highlights: Conducting randomized trials is a major challenge in ultra-rare sarcomas (URS) Thus, external control data (ECD) are critical to let new drug development in URS. Observational retrospective studies (RS) may be the best source of ECD in URS. Global sarcoma experts met to reach a consensus on how to run high-quality RS in URS. Recommended principles could serve the optimal run of ROS also in other rare tumors. Abstract: Background: In ultra-rare sarcomas (URS) the conduction of prospective, randomized trials is challenging. Data from retrospective observational studies (ROS) may represent the best evidence available. ROS implicit limitations led to poor acceptance by the scientific community and regulatory authorities. In this context, an expert panel from the Connective Tissue Oncology Society (CTOS), agreed on the need to establish a set of minimum requirements for conducting high-quality ROS on the activity of systemic therapies in URS. Methods: Representatives from > 25 worldwide sarcoma reference centres met in November 2020 and identified a list of topics summarizing the main issues encountered in ROS on URS. An online survey on these topics was distributed to the panel; results were summarized by descriptive statistics and discussed during a second meeting (November 2021). Results: Topics identified by the panel included the use of ROS results as external control data, the criteria for contributing centers selection, modalities for ensuring a correct pathological diagnosis and radiologic assessment, consistency of surveillance policies across centers, study end-points, risk of data duplication, results publication. Based on the answers to the survey (55 of 62 invited experts) and discussion the panel agreed on 18 statements summarizing principles of recommended practice. Conclusions: These recommendations will be disseminated by CTOS across the sarcoma community and incorporated in future ROS on URS, to maximize their quality and favor their use as control data when results from prospective studies are unavailable. These recommendations could help the optimal conduction of ROS also in other rare tumors.